Comparison of point and roadside transect methods to evaluate the abundance and richness of diurnal raptors in the arid region of Rajasthan. - Govind Tiwari; Puneet Pandey; Rahul Kaul; Hang Lee; Randeep Singh (PLoS ONE)
Diurnal raptors show a wider distribution compared to other groups of birds including passerines, woodpeckers, and seriemas, but occur at lower-than-expected densities. Estimating the precise abundance is essential to achieve conservation goals but the methods used to estimate the populations of birds need to be appropriate to arrive at meaningful conclusions. We compared the two survey methods: roadside point count and strip transects, for estimating species richness and abundance of raptors in the arid landscape of Rajasthan. Roadside point counts and roadside strip transects were done on 50 transects between December 2019- February 2020 (with an average length of 20 km and a total distance of 3000 km) to assess the species richness and abundance of raptors. A total of 2954 observations of raptors belonging to 35 species were recorded using both methods. Mann Whitney U test result showed no significant difference in species richness and abundance estimates between both methods (p = 0.206). The point count method yielded a higher relative abundance of 2.79 individuals [10 km2]-1h-1 than the 1.90 individuals [10 km2]-1h-1 obtained during the strip transect. Also, the number of unidentified species were less for point counts. Extrapolation values indicated that both the methods do not differ much for the detection of unsampled species. The choice of survey method depends on the objectives of the study, but our results favor the use of point counts rather than strip transects to survey raptors in open habitats. The information generated from this study is expected to provide the most efficient method to study the abundance and distribution of raptors in similar landscapes.